Resolução de problemas em contextos de ensino de Matemática: uma abordagem por meio da Teoria dos Grafos - Pezeta, Jefferson Ricart (2013)
Problem solving has been the subject of studies and research in order to define strategies to facilitate actions in its resolution. The graph theory is presented as a strategy that enables the modeling and solving problems, especially those that address issues related to economic paths, coloring, counting, among others, in the context of mathematics, providing a means for the student to structure and model the thinking and actions of resolution. This study is an investigation into the use of graphs as a theoretical basis in solving problems, students performed with the second and third year of high school Boni Consilii School, located in the city of São Paulo, in the district Champs Elysées. The thoughts and observations of the students are brought along the text, favoring analyzes that took into account the students' difficulties in solving problems and possibilities of Graphs in formalization and modeling strategies. In conjunction with Graph Theory, authors like Polya and Brousseau had representative participation in theoretical workshops and strategies applied in the preparation of the sequences that were prepared